Integral attack on MIBS block cipher - Zhi-shu PAN; Jian-sheng GUO; Jin-ke CAO; Wei LUO (Tongxin xuebao)
The security of the block cipher MIBS against integral attack was analyzed and a 5-round distinguisher of MIBS was founded. Considering the equivalent structure of Feistel structure and the relation of master key and round key in the key expansion algorithm of MIBS, it applied integral attack to 10 rounds of MIBS and gave the attack algorithm. The data and time complexities of 10 round attack on MIBS-64 are 228and 252.7respectively. The data and time com-plexities of 10 round attack on MIBS-80 are 2 28.2and 2 53.2respectively. These results demonstrate that integral attack on 10-round MIBS is no immunity, both rounds and data complexity of this integral attack are better than the integral at-tack existing.